ASSESSMENT OF TEACHERS’ WORK – EXPECTATIONS AND REALITY: THE CASE STUDY OF REZEKNE - Kronberga, Ginta; Dzene, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Teachers play a very important role in the education system, as these people are subject to the requirements, constraints, and changes imposed by the education system and, at the same time, they are responsible for the quality education of pupils. Teachers are most directly confronted with the reality in existing educational institutions (in co-operation with colleagues, local authorities, parents of pupils, employers and acting in accordance with legislation) and with the shortcomings in the education system. The educational system in Latvia faces new challenges: liquidation and reorganization of schools, work in combined classes, the need to adapt and respond to educational system reforms. Teachers’ work is subject to constant change; but is it evaluated according to efforts teachers are making? The aim of the article is to investigate the expectations and reality of teachers of primary schools in Rezekne in relation to the assessment of their work. The paper uses a combined research approach: a qualitative research method – semi-structured interviews and a quantitative survey questionnaire. The teachers' expectations regarding job evaluation are related to pay, equity, support, and changes in the education system. Teachers of Rezekne district primary schools are least satisfied with the assessment of the work by the state - teachers are not satisfied with wages and unfairness. The most important thing for teachers is the assessment of pupils, employers and school administrations, as well as parents of pupils.